Gestão de portfólio de projetos de inovação: análise das práticas adotadas por uma empresa de engenharia de grande porte - Borba, Maicon Carvalho de (Universidade do Vale do Rio dos Sinos, 2023)
Organizations use projects to develop their strategies, using them as a tool for innovation, search for new markets and competitiveness. Therefore, in order to achieve the objectives, carrying out an adequate project, which provides reliable information and brings expected returns after completion, is a decisive factor for organizational success. Portfolio management seeks to provide, through practices, the expected results with the application of projects and, in the case of innovation projects, to qualitatively analyze the expected returns, in a scenario of constant uncertainties. Given this, selecting and conducting a portfolio of innovation projects is a challenge for organizations inclined to innovate their products and processes. This research aimed to identify the practices used for portfolio management of innovation projects in a large organization, comparing the results found with what the literature practices according to the project typology. With the application of the case study, it was possible to identify the practices used by the organization, comparing with the existing literature on project portfolio management, focusing on innovation projects. The research results point to the use of qualitative data for portfolio management of innovation projects, which are similar to the tools and techniques described in the literature, however, they do not show standardized practices for portfolio management of innovation projects and the experience of top management is a decisive factor in the selection of projects. For traditional projects, some financial practices, outlined in the literature, are applied according to the results of the case study. With regard to portfolio balancing, there is no defined process according to the typology of projects, diverging from what the literature recommends. Therefore, the findings indicate that there are no standardized practices for portfolio management of innovation projects and project portfolio balancing, which can be characterized as an opportunity for improvement to advance performance, as well as a challenge to be faced in order to achieve standardization of innovation portfolio analyses.
Keywords: Gestão de portfólio; Portfólio de projetos de inovação; Seleção de projetos; Portfolio management; Portfolio of innovation projects; Project selection; ACCNPQ::Engenharias::Engenharia de Produção